CHANGE MANAGEMENT IN GASTRONOMY AND RESTORATION - Đurović, Mladenka; Božić, Aleksandar (The Business of Tourism, 2021)
Modern trends in gastronomy and restaurant business are focused on several key issues: business in accordance with the concept of sustainability, energy efficiency and the use of renewable energy sources, "green" business”, "green" and eco certification, environmental protection, waste reduction and the promotion of healthy eating. However, the changes that are most apparent to the users of the services are the changes in the gastronomic offer, and these are most often new dishes, with the introduction of integral cereals, low-fat and low-energy dishes, food for diabetics, vegetarian dishes, gluten-free food and more. Especially popular is the kitchen based on the use of organic food products and microgreens, and new trend known as molecular gastronomy. In a dynamic market environment in which restaurants operate, contemporary trends impose the need for constant change, and these changes also condition changes in these objects management. Therefore, the manager of restaurant has become a key factor in successful business, which requires serious knowledge in the field of gastronomy and restaurant business. Its main tasks are to make decisions and control their implementation.
Keywords: changes; gastronomy; hospitality; management; restaurant business